Psychometric Properties of the Child Feeding Scale in Turkish Mothers - Sevinç Polat, PhD, RN; Behice Erci, PhD, RN (Elsevier, 2010)
The objective of this study was to adopt the Child Feeding Scale (CFS) to the Turkish language and culture and to assess the validity and the reliability of the Turkish version of the scale. Methods: The research was methodological study design. A convenience sample of 158 mothers at a primary health care center completed a structured questionnaire including the CFS for mothers in 2008. Results: In the assessment of construct validity, seven factors were identified; they related to Perceived Responsibility, Perceived Parent Weight, Perceived Child Weight, Concern About Child Weight, Pressure to Eat, Restriction, and Monitoring. The seven factors explained 57.6% of the total variance. The overall internal reliability coefficient of this scale was .75. Conclusions: The present study provides evidence of the CFS's validity and reliability. The scale has potential applications for use in research. The CFS can be used to assess aspects of child-feeding perceptions, attitudes, and practices and their relationships to children's developing food acceptance patterns, the control of food intake and obesity.